Psychological stress and its relationship life Satisfaction among a sample of male and female students at Taif University - Alzahrani, Amjad Ahmed; Alharthi, Suha Omar (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify psychological stress and its relationship to life Satisfaction among a sample of students from Taif University, and to reveal the differences in the level of psychological pressure and life Satisfaction among the sample members that are attributed to the variables of gender and specialization, and the study used the relational descriptive approach, and the sample consisted of (244) A male and female undergraduate student at Taif University, and the tools used included the Perceived Psychological stress Scale prepared by Al-Zahrani (2018), the life Satisfaction Scale prepared by Desouki (2013).The study found the following results: There is a statistically significant correlation between psychological stress and life Satisfaction, and there are statistically significant differences in the level of psychological stress and life Satisfaction due to the gender variable, where females were more feeling stress and less in life Satisfaction. There are no statistically significant differences in the level of psychological stress and life Satisfaction among the sample members due to the variable of specialization. The study ended with a few recommendations including the establishment of guidance programs to train university students in ways and methods to reduce psychological stress.
Keywords: Life Satisfaction; Students at Taif University; Psychological stress